Management of hemorrhage in maxillofacial injuries using foley's catheter - A review of literature - Merlyn Elizabeth Monsy; Sumir Gandhi; Inderjot Singh; Tarun Koshy Isaac; Angel Subramanium; Rik Mukherjee (Wolters Kluwer Medknow Publications, 2022)
As globalization and digitalization takes place in today's time, wars also advance both in technology along with the arms being used. In today's date, wars are not confined to swords and cannons as it was in traditional warfare, rather the weapons used today are more inclined to injure and wound the population than to kill, thus making the treatment a challenge for the surgeons and clinicians present on the battle ground with the limited resources available.This review was conducted to understand the use of Foley's catheter, which is readily available at all trauma centers for the immediate management of bleeding in penetrating injuries of head and neck region. Methodology: An in-depth search was conducted on Google Scholar and PubMed data bases in an organized order to summarize the final results. Since Foley's catheter is a readily available tool and requires minimal skills for placement, it can be used to as temporary balloon tamponade to control bleeding and hemorrhage on the battle field as an emergency protocol. However, there is a need to develop definite international guidelines and further literature should be worked upon the same for the better understanding of this technique.